Peningkatan Motivasi Belajar melalui Pendekatan Bermain pada Pembelajaran PJOK Kelas VI B SDN Lidah Kulon 1 - Ilham Nur Ardian; Imam Asy'ari; Imam Fahruddin; Ihda Nazidatin Ihtiana; Haryo Witanto; Anung Priambodo; Anang Thohari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study shows that the use of a play-based approach has proven effective in increasing students' learning motivation in Physical Education, Sports, and Health subjects. The research findings reveal that play activities encourage students to be more physically active and to pay more attention to their physical health. Through the implementation of classroom action research over two cycles, it was found that this approach can serve as an effective alternative to enhance students’ active participation in PJOK learning. Based on data collected through observation, documentation, and questionnaires, a significant increase in learning motivation was observed after the play-based approach was applied. The conclusion of this study states that the play-based approach has great potential in fostering interest and enthusiasm for learning among sixth-grade students in class VI D at SD Negeri Lidah Kulon 1 Surabaya in PJOK lessons. Therefore, this approach is recommended for creating a more enjoyable and effective learning atmosphere.